FINANCIAL PERFORMANCE OF THE SURABAYA GOVERNMENT BEFORE AND DURING THE COVID-19 PANDEMIC - Clairine Peggy Dianita; Sri Trisnaningsih (International Journal of Economy, Education and Entrepreneurship, 2023)
This study aims to compare the financial performance of the Surabaya Government before and during the COVID-19 pandemic to identify any differences. The research method used is the quantitative analysis. The data is secondary in Budget Realization Reports for 2018-2021. The population in this study is the Surabaya City Budget Realization Report for 4 years from 2018 to 2021. The sample used in this study is a budget realization report in the form of local own-source revenue budget, local own-source revenue realization, regional revenue realization, transfer revenue realization, regional expenditure budget, and regional expenditure realization; the data analysis technique in this study is the Paired samples t-test. The test results show differences in Surabaya’s financial performance in the degree of fiscal decentralization ratio and the Local Own-source Revenue effectiveness ratio. However, there is no distinction between the ratios of regional financial independence, regional financial efficiency, and economic expenditure ratio